Nutrients and phytoplankton in semienclosed lagoon systems in Florida Bay and their responses to changes in flow from Everglades restoration. (12th June 2017) - Shangguan, Yini; Glibert, Patricia M.; Alexander, Jeffrey A.; Madden, Christopher J.; Murasko, Susan
Abstract: The largest estuarine flow restoration project is the Comprehensive Everglades Restoration Plan (CERP). In 2012, one of its first phases, the C‐111 Project, was initiated and designed to increase freshwater flow into northern Florida Bay. Effects of changes in flow and associated nutrients on phytoplankton abundance and composition were studied in two sets of interconnected, quasi‐enclosed saline lakes at the southern end of the Everglades that discharge into northern Florida Bay. After C‐111 implementation, total dissolved nitrogen (TDN) decreased, driven by especially large declines in NO x − . In spite of N reduction, those lakes that has been oligotrophic prior to the project experienced an approximate doubling of phytoplankton biomass as nutrient ratios converged on Redfield proportions, and a shift to smaller sized cells and a loss of diatoms as NO x − availability declined. The other set of these lakes, previously highly eutrophic, sustained a significant, nearly 50%, decline in overall phytoplankton biomass, particularly larger sized cells, which, in turn, increased downstream. A chemostat model was invoked to explain these changes based on changes in flow and nutrients. In both systems the proportions of picocyanobacteria increased in the upper lakes as the relative availability of chemically reduced forms of N increased. Both lake systems may export algal biomass, changing the phytoplankton assemblage in northern Florida Bay. These lakes may also serve as buffers, damping the effects in Florida Bay itself, and they illustrate broad implications for estuaries that are impacted by natural or anthropogenic changes in flow.